2021
DOI: 10.24072/pcjournal.70
|View full text |Cite
|
Sign up to set email alerts
|

A bird’s white-eye view on avian sex chromosome evolution

Abstract: Chromosomal organization is relatively stable among avian species, especially with regards to sex chromosomes. Members of the large Sylvioidea clade however have a pair of neo-sex chromosomes which is unique to this clade and originate from a parallel translocation of a region of the ancestral 4A chromosome on both W and Z chromosomes. Here, we took advantage of this unusual event to study the early stages of sex chromosome evolution. To do so, we sequenced a female (ZW) of two Sylvioidea species, a Zosterops … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 157 publications
(176 reference statements)
3
25
0
Order By: Relevance
“…A recent study on white‐eyes ( Zosterops spp. ), another Sylvioidea genus that shares the same neo‐sex chromosome system as the great reed warbler, also found that added‐Z genes and autosomal genes had similar dN/dS values despite the lower recombination rate on chromosome Z (as inferred from low GC content, Leroy et al, 2021). Further, a neo‐sex chromosome in monarch butterfly ( Danaus plexippus ) showed evolutionary rate variation depending on both the age of sex‐linkage (added‐ and ancestral‐Z regions) and the gene expression pattern, highlighting the role of other factors in addition to recombination affecting these rates (Mongue et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…A recent study on white‐eyes ( Zosterops spp. ), another Sylvioidea genus that shares the same neo‐sex chromosome system as the great reed warbler, also found that added‐Z genes and autosomal genes had similar dN/dS values despite the lower recombination rate on chromosome Z (as inferred from low GC content, Leroy et al, 2021). Further, a neo‐sex chromosome in monarch butterfly ( Danaus plexippus ) showed evolutionary rate variation depending on both the age of sex‐linkage (added‐ and ancestral‐Z regions) and the gene expression pattern, highlighting the role of other factors in addition to recombination affecting these rates (Mongue et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Previous work on several other Sylvioidea species has, however, already confirmed that the 9.6 Mb-end of the translocated part of chromosome 4A has fused to the 72.9 Mb-end of chromosome Z (i.e. Z 0-72.9(+) -4A 9.6-0(−) ; Leroy et al, 2021;Sigeman et al, 2021) and that the remaining part of chromosome 4A segregates as an independent autosome (Ponnikas et al, 2022). Therefore, we assume that this is also the situation in Sylvietta.…”
Section: Re Sults and Discussionmentioning
confidence: 98%
“…The avian ZW sex chromosome system was long viewed as extremely stable (Nanda et al, 2008). However, recent discoveries of neo-sex chromosomes have revealed that avian sex chromosomes are more variable than was previously believed (Burley et al, 2022;Dierickx et al, 2020;Gan et al, 2019;Huang et al, 2021;Kretschmer et al, 2020;Leroy et al, 2021;Pala, Naurin, et al, 2012;Sardell, 2016;Sigeman et al, 2019Sigeman et al, , 2020. The most diverse avian sex chromosomes currently known are found among members of the Sylvioidea (Dierickx et al, 2020;Leroy et al, 2021;Sigeman et al, 2019Sigeman et al, , 2020.…”
mentioning
confidence: 99%
“…However, there were a few outlier regions for both statistics; first, F ST estimates were slightly higher on the Z chromosome, and second, part of the 4A chromosome shows elevated values of D XY in both the Abyssinian Catbird and the Ethiopian White‐eye. These increased relative values of D XY in these two taxa are expected, as part of the Zebra Finch chromosome 4A has been shown to be part of a neo‐sex chromosome region in the Sylvioidea clade (Leroy et al, 2019) sensu Oliveros et al (2019). We may expect higher genetic differentiation on sex chromosomes due to their lower relative effective population size compared to autosomes and the propensity for sex chromosomes to accumulate structural variants (e.g., Hooper et al, 2018).…”
Section: Resultsmentioning
confidence: 71%